Student Participation in University and Law School Governance - George P. Smith II (Washington University Law Quarterly, 1976)
This Article will examine the means by which American law schools have permitted reasonable student participation without threatening the academic freedom of law school faculties, a threat which the European experience reminds us is very real.
Keywords: Colleges and universities; Law schools